2012
DOI: 10.1134/s0030400x12060057
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-mechanical calculations of the intensity distribution in spectra of adenine tautomers: I. Spectra of resonant hyper-Raman scattering

Abstract: The spectra of resonant hyper Raman scattering of five tautomeric forms of adenine have been theoretically determined for the first time based on quantum mechanical calculations in the Herzberg-Teller approximation. The occurrence of three structures, Ade N 9 ,N 1 H + , Ade N 9 H(am), and Ade N 7 H(am), in an aqueous solution of adenine has been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Different spectroscopic techniques, containing microwave spectroscopy, matrix-isolated spectroscopy, double resonance spectroscopy, IR spectroscopy, NMR spectroscopy, and photoelectron spectroscopy, have been used to investigate adenine and its derivatives in the isolated molecule state, the solid state, and aqueous solution. But the key problem is how to build the relation between tautomerization and vibrational spectra in experimental and theoretical studies. A few of theoretical studies have been reported on halogen substituted at the C 8 position of adenine, but these studies mainly focused on changes of tautomerism, electronic structures, protonation and deprotonation, as well as the influence of the substituent effect on the hydrogen bonding interaction. Ladik and Bcizó studied the charge distribution of series of substituted adenine at the SCF MO level for understanding the nucleotide base antimetabolite-type possible anticarcinogenic activity in 1970 .…”
Section: Introductionmentioning
confidence: 99%
“…Different spectroscopic techniques, containing microwave spectroscopy, matrix-isolated spectroscopy, double resonance spectroscopy, IR spectroscopy, NMR spectroscopy, and photoelectron spectroscopy, have been used to investigate adenine and its derivatives in the isolated molecule state, the solid state, and aqueous solution. But the key problem is how to build the relation between tautomerization and vibrational spectra in experimental and theoretical studies. A few of theoretical studies have been reported on halogen substituted at the C 8 position of adenine, but these studies mainly focused on changes of tautomerism, electronic structures, protonation and deprotonation, as well as the influence of the substituent effect on the hydrogen bonding interaction. Ladik and Bcizó studied the charge distribution of series of substituted adenine at the SCF MO level for understanding the nucleotide base antimetabolite-type possible anticarcinogenic activity in 1970 .…”
Section: Introductionmentioning
confidence: 99%